Investigating IT Governance through the Viable System Model. Issue 2 (3rd April 2019) - Huygh, Tim; De Haes, Steven
ABSTRACT: This paper investigates IT governance through the Viable System Model (VSM). We make a theoretical contribution by discussing why IT governance can continue to achieve its purpose of creating and preserving IT business value. Additionally, we demonstrate how the VSM can be used as a lens to describe and diagnose IT governance from a practical perspective, offering insights in how complexity can be unfolded and how complexity engineering takes place to handle changing complexity.